Faktor Berhubungan dengan Pemberian Vitamin A - Angraini, Wulan; Oktavianti, Elia; Febriawati, Henni; Husin, Hasan; Sarkawi, Sarkawi; Agustinawati, Zulaikha (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Vitamin A is the most important nutrient, vitamin A has various uses in various ways to reduce mortality and the risk of disease. The Ministry of Health establishes public health policies and Vitamin A supplementation programs in the field. The process begins with preparation, continues with the provision of vitamin A capsules, and ends with delivery to the intended recipients, namely infants and toddlers. The main objective of this study was to determine what variables are related to the provision of vitamin A in the Kuala Lempuing Health Center work area, Bengkulu City. After data collection, the number of valid samples that met the inclusion and exclusion criteria was 45 samples, based on the initial sample of 76 respondents selected using the Accidental Sampling technique. Based on the results of the analysis, several variables were found that were related to the provision of vitamin A and several variables that were not related. The variables of knowledge and the role of cadres were related (each p = 0.038 and p = 0.023), while the relationship (each p = 0.057), distance (each p = 1000), and family support (each p = 0.454) were not related. The function of cadres in providing vitamin A is significantly related to the knowledge factor. Vitamin A and the increasing responsibility of cadres to provide it to toddlers should be the subject of routine counseling. Keywords: Knowledge, Attitude, Distance, Family Support, Role of Cadres, Vitamin A  ABSTRAK Vitamin A merupakan zat gizi yang paling penting, vitamin A memiliki bermacam kegunaan dalam berbagai cara untuk mengurangi angka kematian dan resiko penyakit. Kementrian kesehatan menetapkan kebijakan kesehatan masyarakat dan program sumplementasi Vitamin a di lapangan. Proses dimulai dari persiapan, dilanjutkan dengan pemberian kapsul vitamin A, dan diakhiri dengan penyerahan kepada penerima yang dituju, yaitu bayi dan balita.  Tujuan utama penelitian ini untuk mengetahui variabel apa saja yang berhubungan dengan pemberian vitamin A di wilayah kerja Puskesmas Kuala Lempuing Kota Bengkulu. Setelah dilakukan pengumpulan data, diperoleh total sampel valid dengan kriteria inklusi maupun eksklusi sebanyak 45 sampel, berdasarkan sampel awal sebanyak 76 responden yang dipilih dengan teknik Accidental Sampling. Berdasarkan hasil analisis, ditemukan beberapa variabel terkait pemberian vitamin A dan beberapa variabel yang tidak berhubungan. Variabel pengetahuan dan peran kader terdapat hubungan (masing-masing p=0,038 dan p=0,023), sedangkan keterkaitan (masing-masing p=0,057), jarak (masing-masing p=1000), dan dukungan keluarga (masing-masing p=0,454) tidak terdapat hubungan. Fungsi kader dalam pemberian vitamin A berhubungan signifikan dengan faktor pengetahuan. Vitamin A dan meningkatnya tanggung jawab kader untuk menyediakannya kepada balita harus menjadi subjek konseling rutin. Kata Kunci: Pengetahuan, Sikap, Jarak, Dukungan Keluarga, Peran Kader, Vitamin A